Perilaku Remaja Pengguna Lensa Kontak (Soft Lens) dalam Perawatan Kesehatan Mata di SMKN 3 Kota Blitar - Sunarti Sunarti; Wahyu Setianingsih (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
The use of contact lenses an alternative to eyeglasses. Lensa tools contacts could be supporting the appeal and appearance of a person to be more stylish and different. In the opinion of one ophthalmologist in dr Soetomo there are 50% of patients with eye disorders contact lens contaminated by amoebas and 1% of patients experienced a severe disorder that causes permanent blindness. The use of contact lenses require secure the right under the guidelines. The aim of research to study the behavior of adolescent users of contact lenses (soft contact lens) in the eye health care in SMK N 3 of Blitar. The study population were students of class XI and the sample studied class XI students who wear contact lenses, using purposive sampling technique. The collection of data by means of a checklist and interview. The results showed as much as 37.1% to behave according to the SOP by 45.7% in the use of contact lenses, but 62.9% showed no behavior according to SOP in the cleaning of contact lenses. This is due to adolescents do not get used to the consultation eye health workers. Recommendations of this study are expected to educational institutions in collaboration with health care providers in improving the UKS program for health promotion in particular about the behavior in the use and cleaning of contact lenses in accordance with the SOP.